(untitled) (Current Problems in Rail Vehicles, 2025)
The paper deals with the practical use of simplified 2-mass and 3-mass damped dynamic models in the optimization of suspension design of a rail vehicle. The text follows previous paper presented at the XXVI. International Conference PRORAIL 2023 in Žilina. The paper deals with the simulation of the travel of a 2-mass and 3-mass damped model on real measured track irregularities with the evaluation of various indicators of comfort on the carbody and the optimization of stiffness and damping characteristics in the secondary suspension. The paper calculates the following comfort indexes: the standard method of mean comfort NMV, the complete method of mean comfort NVD and the permanent comfort CCz according to EN 12299. Finally, paper presents a comparison of the optimization results of the characteristics of secondary dampers for individual comfort indexes for various track irregularities and running speeds.